Sugen–morphine model of pulmonary arterial hypertension. (1st January 2020) - Agarwal, Stuti; Harter, Zachery J.; Krishnamachary, Balaji; Chen, Ling; Nguyen, Tyler; Voelkel, Norbert F.; Dhillon, Navneet K.
Abstract : Pulmonary arterial hypertension is a fatal disease associated with pulmonary vascular remodeling and right ventricular hypertrophy. Pre‐clinical animal models that reproduce the human pulmonary arterial hypertension process and pharmacological response to available therapies are critical for future drug development. The most prevalent animal model reproducing many aspects of angioobliterative forms of pulmonary arterial hypertension is the rat Sugen/hypoxia model in which Sugen, a vascular endothelial growth factor receptor antagonist, primarily causes initiation of endothelial injury and later in the presence of hypoxia promotes proliferation of apoptosis‐resistant endothelial cells. We previously demonstrated that exposure of human pulmonary microvascular endothelium to morphine and HIV‐proteins results in initial apoptosis followed by increased proliferation. Here, we demonstrate that the double‐hit of morphine and Sugen 5416 (Sugen–morphine) in rats leads to the development of pulmonary arterial hypertension with significant medial hypertrophy of pre‐acinar pulmonary arteries along with neo‐intimal thickening of intra‐acinar vessels. In addition, the pulmonary smooth muscle and endothelial cells isolated from Sugen–morphine rats showed hyperproliferation and apoptotic resistance, respectively, in response to serum starvation. Our findings support that the dual hit model of Sugen 5416 and morphine provides another experimental strategy to induce significant pulmonary vascular remodeling and development of severe pulmonary arterial hypertension pathology in rats without exposure to hypoxia.